Chitosan oligosaccharide suppresses tumor progression in a mouse model of colitis-associated colorectal cancer through AMPK activation and suppression of NF-κB and mTOR signaling. (10th July 2016) - Mattaveewong, Tharinee; Wongkrasant, Preedajit; Chanchai, Sumalee; Pichyangkura, Rath; Chatsudthipong, Varanuj; Muanprasat, Chatchai
Highlights: Chitosan oligosaccharides (COS) inhibited colorectal cancer growth in mice. COS stimulated AMPK and suppressed NF-κB and mTOR signaling in colon tissues. COS inhibited MMP-9 expression. Oral administration of COS showed no systemic toxicity in mice. Abstract: Novel, effective and safe agents are needed for the chemoprevention of colorectal cancer (CRC). This study investigated the effects of chitosan oligosaccharides (COS) on CRC progression and their underlying mechanisms and safety profiles in mice. Using a mouse model of colitis-associated CRC, we found that oral administration of COS (500 mg/kg/day) resulted in a ∼60% reduction of tumor size and tumor numbers/sectioning. In addition, COS treatment increased AMPK activity, suppressed the NF-κB-mediated inflammatory response and reduced the expressions of cyclin D1, phosphorylated ribosomal protein S6, and MMP-9 in the colon tissues of these mice. Importantly, administration of COS (500 mg/kg/day; 50 days) had no adverse effects on renal or liver functions. Our results indicate that COS suppressed CRC progression via AMPK activation and the suppression of NF-κB and mTOR signaling. COS may be of potential utility in the chemoprevention of CRC.